2007
DOI: 10.1007/s11783-007-0072-7
|View full text |Cite
|
Sign up to set email alerts
|

A simple and cheap method for preparation of coupled ZrO2/ZnO with high photocatalytic activities

Abstract: The objective of this study was to prepare a new photocatalyst with high activities for degradation of organic pollutants. Coupled ZrO 2 /ZnO photocatalyst was prepared with a simple precipitation method with cheap raw materials zinc acetate and zirconium oxychloride, and was characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM). Reactive brilliant red X-3B was used as a model compound to investigate the photocatalytic activity of synthesized catalysts in water under 254 nm UV irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Under solar radiation, La 3+-TiO 2 containing 0.4 mol % lanthanum showed highest surface area(124.8 m 2 /g), lowest crystallite size (8 nm), and exhibited 50% more degradation of Methylene Blue compared with pure TiO 2 (Parida and Sahu 2008). Zheng et al (2007) noticed that the coupled ZrO 2 -ZnO system with 2.5% Zr was more efficient compared with ZnO for the degradation of reactive Brilliant Red X-3B. Wen et al (2009) investigated the effects of I and F codoped TiO 2 (prepared by sol-gel-impregnation method) on the photocatalytic degradation of MB.…”
Section: Doping and Mixed Semiconductormentioning
confidence: 94%
See 2 more Smart Citations
“…Under solar radiation, La 3+-TiO 2 containing 0.4 mol % lanthanum showed highest surface area(124.8 m 2 /g), lowest crystallite size (8 nm), and exhibited 50% more degradation of Methylene Blue compared with pure TiO 2 (Parida and Sahu 2008). Zheng et al (2007) noticed that the coupled ZrO 2 -ZnO system with 2.5% Zr was more efficient compared with ZnO for the degradation of reactive Brilliant Red X-3B. Wen et al (2009) investigated the effects of I and F codoped TiO 2 (prepared by sol-gel-impregnation method) on the photocatalytic degradation of MB.…”
Section: Doping and Mixed Semiconductormentioning
confidence: 94%
“…In the presence of P25, Selvam et al (2007) indicated that complete degradation of 4-flurophenol with P25 was achieved in 60 min while complete degradation occurred in 90 min in the presence of ZnO. Zheng et al 2007 compared the photocatalytic degradation of reactive brilliant red X-3B in water with pure ZnO, ZrO 2 -ZnO, and P25 TiO 2 . The degradation of reactive brilliant red over coupled ZrO 2 -ZnO was shown to be higher compared with pure ZnO and also slightly better than that of P25 and TiO 2 .…”
Section: Crystal Composition and Catalyst Typementioning
confidence: 99%
See 1 more Smart Citation
“…Many photocatalytic systems use semiconductor particles, such as TiO2, ZnO, ZnS, Fe2O3, CdS and CeO2. Although TiO2 is generally considered to be the most active photocatalyst [4][5][6], ZnO is also regarded as a promising contender. The photocatalytic material can promote an electron in the conduction band and generate positive hole in the valence band if material is excited by the absorption of electromagnetic radiation with energy E ≥ Eg.…”
Section: Introductionmentioning
confidence: 99%
“…The creation of wide zone semiconductor materials that can produce simultaneously hydroxyl radicals and superoxide radicals, from usual materials by simple technology is not only interesting but also very useful. In our opinion, zirconia nanoparticles can be used as a base material for the creation of composite materials, since they are characterised by a wide (more than 5 eV) band gap, a conduction band potential of -1.0 V vs. NHE at pH = 0, and a valence band potential of +4.0 V vs. NHE [9], Unfortunately, studies that mention ZrO2-ZnO, ZrO2-TiO2 and Fe/ZrO2 composites are very limited [4,8,10,11].…”
Section: Introductionmentioning
confidence: 99%